Skapandet av ett pedagogiskt VR-spel: Ett Escape room-spel för utställningen "Alla kan innovera" - Grennberg, Lisa; Kullberg, Amanda (My University, 2019)
This report examines the possibility to use Virtual Reality as an educational tool to increase children's dedication to learn. VR has been discovered to be a powerful technique used to capture its users’ full attention and at the same time push them outside their comfort zones. This project has explored the usage of the combination between VR and the benefits from gamification, Escape rooms and game design to enlighten history in a new innovative way. The background to this project started with RISE Interactives strive to show that everyone can innovate and to demonstrate that we have to implement an interdisciplinary approach to solve future challenges. It was decided to try and create a new type of VR-game where three people can play and interact together in the virtual world while they at the same time exist together in the physical room. The purpose with this project is to create a thrilling narrative with tricky puzzles that appeals to the target group set to be children in the age of 10. The main focus is to design appropriate avatars that fits both the game's specific narratives and can contribute to enhance the importance of interdisciplinarity and innovation. The methods implemented in the design process are well established methods within product development and game design. They have been chosen wisely and consists of both information gathering and a more analytic course of action. Most of the information gathering methods have been used to get a deeper understanding for the target group's needs and demands while the analytic methods are used to define general design guidelines to help generate relevant ideas. In the end of the report the final result, a first prototype of a VR-game, was tested by its users installed as a part of a new museum exhibition “The future was here ” at Borås Museum. In addition to the game prototype, a result of this project is also six modulated avatars with theme appropriate clothing and hairstyles together with a few modulated objects that are important for the narrative. At last this project resulted in a theoretical design for a second level to the game that hopefully in the near future also will become reality. In conclusion this report shows that it is possible to create a combination between VR and an Escape room to enlighten history, increase players learning ability and show the importance of collaboration and interdisciplinarity.
Keywords: Virtual Reality, gamification, game design, avatar-development, Escape room